2008
DOI: 10.2500/ajr.2008.22.3143
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Postural Change on Nasal Airway and Autonomic Nervous System Established by Rhinomanometry and Heart Rate Variability Analysis

Abstract: The central ANS activities significantly correlated with changes to the nasal airway during postural change. The central ANS, especially the sympathetic nervous system, may play a role in controlling nasal airway during postural change.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 27 publications
1
25
0
Order By: Relevance
“…They have found that HRV is decreased in these patients. However, Ko et al (2008) showed that total nasal airflow was significantly decreased and the total nasal airway resistance was significantly increased, and nasal airway changes were significantly correlated with central autonomic system responses in patients with allergic rhinitis. SNN50 count, number of R-R intervals exceeding 50 ms; RMSSD, root mean square of successive differences between normal sinus R-R intervals; PNN50, the percentage of difference between adjacent normal R-R intervals that are greater than 50 ms computed over the entire 24-hour ECG recording; HRV triangular index, the ratio of number of all R-R intervals to the height of histogram created by the charting all the RR intervals; SDANN, the standard deviation of all averaged normal sinus R-R intervals for each 5-minute segment in the 24-hour recordings; SDNN, the standard deviation of all normal sinus R-R intervals over 24 hours; LF, low frequency power; HF, high frequency power; n.u., normalized unit.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…They have found that HRV is decreased in these patients. However, Ko et al (2008) showed that total nasal airflow was significantly decreased and the total nasal airway resistance was significantly increased, and nasal airway changes were significantly correlated with central autonomic system responses in patients with allergic rhinitis. SNN50 count, number of R-R intervals exceeding 50 ms; RMSSD, root mean square of successive differences between normal sinus R-R intervals; PNN50, the percentage of difference between adjacent normal R-R intervals that are greater than 50 ms computed over the entire 24-hour ECG recording; HRV triangular index, the ratio of number of all R-R intervals to the height of histogram created by the charting all the RR intervals; SDANN, the standard deviation of all averaged normal sinus R-R intervals for each 5-minute segment in the 24-hour recordings; SDNN, the standard deviation of all normal sinus R-R intervals over 24 hours; LF, low frequency power; HF, high frequency power; n.u., normalized unit.…”
Section: Discussionmentioning
confidence: 95%
“…A recent study focused on the relationships between nasal ANS and central ANS maintaining cardiovascular hemodynamics revealed that the central ANS activities correlate with the nasal obstruction induced by the postural changes (Ko et al 2008). It has been suggested that the central ANS, especially the sympathetic nervous system, is involved in the mechanism.…”
Section: Tohoku University Medical Pressmentioning
confidence: 99%
“…The correlation was significant using Pearson's correlation analysis (R = 0.44, P \ 0.01) hydrostatic pressure in the sinusoid vessels [12] and/or from venous stasis combined with atony of the minor vessels and ANS changes [13]. In a previous study, central ANS activity showed a significant correlation with nasal airflow during postural change [14]. In this study, UNB was associated with a significant increase in nasal airway resistance and a decrease in sympathetic activity.…”
Section: Discussionmentioning
confidence: 99%
“…The parasympathetic nervous system may play a role in the control of breathing and in the hyperpneic responses associated with airfl ow obstruction. The parasympathetic nervous system component includes neural receptors in the airways as well as afferent and efferent pathways that travel in the vagus nerves (Ko et al 2008 ).…”
Section: Nasal Receptorsmentioning
confidence: 99%